Electronic, elastic, mechanical and anisotropic response of W3XC2 (X: Si, Ge and Al) alloys via first-principles. (15th February 2022) - Güler, E.; Güler, M.; Uğur, Ş.; Özdemir, A.; Uğur, G.
Abstract: First-principles calculations were carried out for the electronic, elastic, mechanical and anisotropic behavior of W3 XC2 (X: Si, Ge and Al) alloys. Electronic bands analyses reveal an obvious metallic character for all of the investigated alloys. In addition, the calculated magnitudes of Young's modulus of the alloys follow the range of W3 SiC2 > W3 AlC2 > W3 GeC2 . Similarly, the hardness values of the alloys also follow the same sequence. Amongst the surveyed alloys, W3 GeC2 has the highest ductility when compared to W3 SiC2 and W3 AlC2 alloys. According to obtained results, the most anisotropic alloy was found to be W3 SiC2 . On the other hand, W3 GeC2 and W3 AlC2 alloys are found to be more machinable than the W3 SiC2 alloy. Highlights: Electronic, elastic and mechanical properties of W3 XC2 (X = Si, Ge, Al) alloys are calculated using the GGA-PBE approach. The electronic band structures reveal metallic characteristics of the studied alloys. Machinability indexes values of W3 XC2 (X = Si, Ge, Al) alloys are predicted to be between 1.49 and 2.35. All of the W3 XC2 (X = Si, Ge, Al) alloys show ductile mechanical behavior. W3 XC2 (X = Si, Ge, Al) alloys are found to be elastically anisotropic.